Swine leptospirosis: the disease and the relation with public health - VAROUDIS (Λ.Β. ΒΑΡΟΥΔΗΣ) V. L.; SAOULIDIS (Κ. ΣΑΟΥΛΙΔΗΣ) K.; SARRIS (Κ. ΣΑΡΡΗΣ) K.; ANTONIADIS (Α. ΑΝΤΩΝΙΑΔΗΣ) A.; KYRIAKIS (Σ.K. ΚΥΡΙΑΚΗΣ) S. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
Swine leptospirosis is an important bacterial disease known from the past century. At present its significance is underestimated contrary to the epidemiological and other scientific evidences. This review is dealing with aetiology, pathogenesis, epidemiology, clinical signs, post mortem findings, diagnosis, treatment and control measures of swine leptospirosis. Finally the relation of leptospirosis, in general, with public health is examined.